Alcohol use disorder hospitalisations over the last two decades: a population‐based cohort study. Issue 3 (March 2016) - Liang, W.; Chikritzhs, T.
Abstract : Background: Alcohol use disorders are risk factors for almost all health conditions due to heavy alcohol use. The epidemiology of alcohol use disorders can be used to monitor harm from heavy alcohol consumption. Aim: To estimate changes in the risk of alcohol use disorders over the last two decades among the Western Australian adult population. Methods: This population‐based cohort study used hospital separation records for Western Australian residents aged 18 years and older that occurred between 1990 and 2013 with a primary diagnosis of alcohol use disorder and annual estimated residential population to estimate the annual gender‐ and age‐specific incidence rate. A random sample of emergency presentations to public hospitals in Western Australia between 2002 and 2013 was used to account for confounding effects, such as changes in patient access to medical care and overall improvement in healthcare service in the multivariable Poisson regression model. Results: The risk of alcohol use disorder hospitalisations among the Western Australia population has increased considerably since 1998 with a decline in 2012 and 2013. The average rate remained significantly higher from 2010 to 2013 compared with previous years. Conclusions: The trend of alcohol use disorder hospitalisations is indicative of an increase in harm due to heavy alcohol use in the population.